2021
DOI: 10.3389/fbioe.2021.661694
|View full text |Cite
|
Sign up to set email alerts
|

Developing Clostridia as Cell Factories for Short- and Medium-Chain Ester Production

Abstract: Short- and medium-chain volatile esters with flavors and fruity fragrances, such as ethyl acetate, butyl acetate, and butyl butyrate, are usually value-added in brewing, food, and pharmacy. The esters can be naturally produced by some microorganisms. As ester-forming reactions are increasingly deeply understood, it is possible to produce esters in non-natural but more potential hosts. Clostridia are a group of important industrial microorganisms since they can produce a variety of volatile organic acids and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 97 publications
(105 reference statements)
0
8
0
Order By: Relevance
“…Besides formation of ethyl acetate, Atf1 is known to have broad alcohol specificity and is able to catalyze formation of other acetate esters, including butyl acetate and hexyl acetate [ 13 , 14 , 32 , 33 ]. To investigate whether an acetogen expressing Atf1 also has potential for biosynthesis of other acetate esters from CO, C. autoethanogenum [P Thl -Atf1] was grown on CO supplemented with either butanol or hexanol and was compared to a reference condition with and without ethanol supplementation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides formation of ethyl acetate, Atf1 is known to have broad alcohol specificity and is able to catalyze formation of other acetate esters, including butyl acetate and hexyl acetate [ 13 , 14 , 32 , 33 ]. To investigate whether an acetogen expressing Atf1 also has potential for biosynthesis of other acetate esters from CO, C. autoethanogenum [P Thl -Atf1] was grown on CO supplemented with either butanol or hexanol and was compared to a reference condition with and without ethanol supplementation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a yield of 5% was reported for ethyl acetate production from glucose by E. coli BW25113 Δ ackA Δ ldhA (DE3) expressing Sce Atf1 [ 11 ]. On the other hand, use of the Sce Atf1 is associated with high-level production of other short-chain esters such as butyl acetate [ 13 ]. For example, up to ca.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol doping shows potential of Atf1 for ester production from CO Besides formation of ethyl acetate, Atf1 is known to have broad alcohol speci city and is able to catalyze formation of other acetate esters, including butyl acetate and hexyl acetate [14,15,30,31]. To investigate whether an acetogen expressing Atf1 also has potential for biosynthesis of other acetate esters from CO, C. autoethanogenum [P Thl -Atf1] was grown on CO supplemented with either butanol or hexanol and was compared to a reference condition with and without ethanol supplementation (Fig.…”
Section: Ethanol Supplementation Boosts Ethyl Acetate Productionmentioning
confidence: 99%
“…For example, 0.1 mM ethyl acetate was produced with supplementation of 100 mM ethanol in E. coli TOPO expressing Atf1 [13], and 5% of the maximum pathway yield for ethyl acetate was achieved in the E. coli BW25113 ΔackAΔldhA (DE3) expressing Atf1 [11]. On the other hand, Atf1 is associated with high-level production of other short-chain esters such as butyl acetate, with, for example, production up to 175 mM in engineered Clostridium saccharoperbutylacetonicum [14,15]. So far only sugar-based microbial production platforms have been explored for short-chain ester production.…”
mentioning
confidence: 99%
“…It has been demonstrated that the assimilation of CO 2 can give bacteria some advantages, such as dissipating the excess of reducing equivalents produced by metabolic processes or accumulating organic molecules as energy and carbon storage [ 6 ]. Among the microorganisms able to use inorganic sources of carbon, clostridia have been extensively investigated over the years due to their metabolic potential for industrial applications, with significant results [ 10 , 11 ]. Different strategies for CO 2 capture, conversion, improvement, and control have been developed, involving genetic engineering, synthetic biology, metabolic engineering, and more recently, microbial electrosynthesis (MES) [ 11 , 12 , 13 ], which operates at the nexus of microbiology and electrochemistry to reduce CO 2 to value-added products [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%